Penerapan Metode Fuzzy Analitycal Hierarchy Process dalam Penetapan Panitera Pengganti di Pengadilan Negeri Malang - Haryuni Siahaan; Nurul Hidayat; Bayu Rahayudi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
In the world of law as in Indonesia, a court is needed to conduct a trial. An institution that has the authority to deal with the case is the District Court, where there are parties who assist in resolving it. The substitute registrar is the party in charge and handles incoming officers. Determination of what is done in choosing who carries out the task is still done by appointment. This results in the appointment of a substitute clerk indirectly affecting the handling of case decisions to be resolved due to several criteria considerations. However, in determining the replacement clerks there is still no assessment for each criterion that will be used so that the results obtained are less than optimal. Fuzzy Analytical Hierarchy Process (F-AHP) is one method that is able to overcome this problem. The test uses the Spearman correlation test method in determining the substitute clerks based on the results of expert rankings with system rankings. The results of testing the level of the system ranking relationship to the ranking of experts using 496 datasets obtained the results of the Spearman correlation average of 0.370376 which means having a moderate relationship. So that it can be concluded that the incompatibility of expert ranking results with system ranking is because there is a large correlation test value that is inversely proportional to the data specified.